Le statut sémantico-discursif de comme je l’ai dit - Rouski, Margarita (Kalbotyra, 2021)
The current paper examines the function of a specific construction comme je l’ai dit and its role in a particular type of oral discourse. The phrase occurs with high frequency in an established discursive genre, namely, debates in the European Parliament (EP). It is presented as a parenthetic construction, including elements with an anaphoric function, and endowed with a specific discursive aim. In order to better understand the raison d’être of this syntactically autonomous form in the specialized corpus, a mixed semantic-discursive approach is adopted. The aim of the study is to highlight the main properties of the construction bearing a particular functionality and to specify its status in discourse from the perspective of the active interlocutor. Given its rather simple morphological paradigm, its rather stereotypical enlargements, and its easy mobility, comme je l’ai dit reveals certain specificities of the referential process. The reference of the anadeictic type causes a sort of “duplication” of the object of discourse and also its reconfiguration. The return to the already said, with the aim of re-modeling it, is in fact accompanied by a re-saying, a repetition of the locutor’s own speech. The interrupting, the going back, the reworking and advancing, involved in the use of the analysed construction, seem to have several implications. The presence of comme je l’ai dit is justified by the speaker’s intention to construct relevant discourse that takes into account intralocutive and interlocutive dialogism. The interruption followed by a relaunch is a signal that redirects the attention of the interlocutor, while the repetition, which is a reminder of the already said, preserves the continuity of the discourse. The two processes set up by comme je l’ai dit, anaphoric reference and repetition, have the function of ensuring the coherence and the continuity of ongoing discourse through the tradeoff between saying, repeating and discursive memory. The importance of adjustments between speaker and interlocutor is the basis of the chosen discursive strategy. The functional perspective brings out the interpersonal aspect of the referential procedure.